Evidence for lightning‐associated enhancement of the ionospheric sporadic E layer dependent on lightning stroke energy. Issue 10 (30th October 2015) - Yu, Bingkun; Xue, Xianghui; Lu, Gaopeng; Ma, Ming; Dou, Xiankang; Qie, Xiushu; Ning, Baiqi; Hu, Lianhuan; Wu, Jianfei; Chi, Yutian
Abstract: In this study we analyze the lightning data obtained by the World‐Wide Lightning Location Network (WWLLN) and hourly ionospheric data observed by ionosondes located at Sanya and Beijing, to examine the changes in ionospheric electron density in response to the underlying thunderstorms and to investigate the possible connection between lightning discharges and the enhancement of the ionospheric sporadic E ( E s ) layer. We identify a statistically significant enhancement and a decrease in altitude of the E s layer at Sanya station, in agreement with the results found at Chilton, UK. However, the lightning‐associated modification of the E s layer investigated using the same approach is not evident at Beijing station. Furthermore, we compare the responses to weak and strong lightning strokes using WWLLN‐determined energies at Sanya in 2012. The lightning‐associated enhancement of the E s layer is predominantly attributed to powerful strokes with high stroke energy. A statistically significant intensification of the E s layer with higher‐energy strokes at Sanya, along with the statistical dependence of lightning‐associated enhancement of the E s layer on stroke energy, leads us to conclude that the magnitude of the enhancement is likely associated with lightning stroke energy. Key Points: E s enhancement related to lighting is more evident at a coastal station E s enhancement might be related to lightning difference between coast and land E s enhancement is possibly related to lightning stroke energy